mpaulafinol10
mpaulafinol10
04-03-2022
Mathematics
contestada
Simplify the expression 11+3(−5+4)
Respuesta :
joycewayo45
joycewayo45
04-03-2022
Answer:
=
11+3(-1)
=
-14
The answer is
-
14
.
Step-by-step explanation:
Please mark me brainliest
Answer Link
VER TODAS LAS RESPUESTAS ( 52+ )
Otras preguntas
Need help with this thanks :)
3.Which equation is equivalent to x + 3y – z = 3? 3x + 6y – 3z = 6 2x + 4y – 2z = 8 4x + 12y – 4z = 12 2x + 3y – 4z = 12 4.Which of the following points lies in
Si el promedio de cuatro numeros impares cosecutivos es 28, entonces el mayor de los numeros corresponde a: a.25b) 26c) 27 d. 28e) ninguna de las anteriores
classical conditioning vs operant
The cost, C, of materials for a deck varies jointly with the width w and the length l. If C = $470.40 when w = 12 and l = 16, find the cost when w = 10 and l =
Jamiya jogged 4.8 miles each day for 21 days last a month. how many miles did she jog last month
The price of mangoes is currently $5.00 per pound. At this price, producers are supplying 4,000 pounds of mangoes. Point C on the graph shows the current equili
What is the length, in units, of the hypotenuse of a right triangle if each of the two legs is 3 units? Square root of 18 units Square root of 27 units 3 uni
please help with geomtry
What are the most common types of cables in a network?